2017
DOI: 10.1057/s41260-017-0060-9
|View full text |Cite
|
Sign up to set email alerts
|

Tail Event Driven ASset allocation: evidence from equity and mutual funds’ markets

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 60 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Bri ere et al (2015) found that cryptocurrencies have different statistical characteristics from oil, gold and other assets. They have also been found to be more volatile but often result in greater returns than traditional assets (Bri ere et al, 2015;H€ ardle et al, 2018a;Srilakshmi and Karpagam, 2017).…”
Section: Data and Samplementioning
confidence: 99%
“…Bri ere et al (2015) found that cryptocurrencies have different statistical characteristics from oil, gold and other assets. They have also been found to be more volatile but often result in greater returns than traditional assets (Bri ere et al, 2015;H€ ardle et al, 2018a;Srilakshmi and Karpagam, 2017).…”
Section: Data and Samplementioning
confidence: 99%
“…Example 3 (Portfolio allocation) A successful asset allocation takes the portfolio tail structure into account. Consider, for example, the Tail Event Driven ASset allocation (TEDAS) framework that was developed by Härdle et al (2015). Generally speaking, TEDAS enables us to broaden the classical portfolio allocation by using quantile regression between the index series and portfolio constituents at selected fixed tail levels (e.g., 5%, 15%, 25%, 35% and 50%).…”
Section: Tail Event Risk Examplesmentioning
confidence: 99%
“…For further details, we refer to Härdle et al (2015). As frequently encountered in risk management, both cases result in relatively short time series due to weekly or monthly rebalancing schemes.…”
Section: Tail Event Risk Examplesmentioning
confidence: 99%